A practical foundation in accounting - Johnson, Harry, 1931-; Whittam, Austin (London : International Thomson Business, 1998)
This book is about: Recording accounting data; Ledger accounts; Trading; Making adjustments; Final accounts; ...
Keywords: Accounting; Accounting; Accounting -- Problems, exercises, etc